Hydrogen production with an auto-thermal MSW steam gasification and direct melting system: A process modeling. (1st February 2022) - Wang, Haiming; Ren, Ranwei; Liu, Bingjie; You, Changfu
Abstract: Municipal solid waste steam gasification and direct melting system is proposed in this study for H2 production and ash melting simultaneously. Part of the H2 generated in gasification is extracted for combustion with pure oxygen in the melting zone to provide the energy necessary for auto-thermal operation. A simulation model is developed with Aspen Plus to investigate the performance and optimum conditions of the system. For the feedstock with a lower heating value of 18.91 MJ/kg used in this study, 39.8% of the generated H2 needs to be extracted to maintain the heat balance of the system at the gasification temperature of 900 °C, melting temperature of 1400 °C, and S/M of 1. The net H2 yield is ∼77.3 kg/t-MSW with a net cold gas efficiency of 49.1% under the same operating condition. An optimum operation condition for T (850–1000 °C) and S/M (0.6–1.0) is determined considering the balance between H2 production ability and the auto-thermal energy balance. Highlights: MSW steam gasification and direct melting is proposed. An Aspen Plus model is developed to simulate the performance of the process. 39.8% of H2 in syngas is combusted with O2 to achieve auto-thermal operation. Highest net H2 yield is 79 kg/t-MSW with a gross cold gas efficiency of 50%.